Final assessment tool quality of the subject Cell, Tissues and Integumentary System - Marlen Llanes Torres; Roxana Gómez Vilela; Galia Ibis Pérez Rumbaut; Laura Naranjo Hernández; Zulema Tamara Mesa Montero; Grey Alicia Crespo Lechuga (Medisur)
Background: when an assessment tool is used, it must conform to rigorous quality standards; defects in its preparation have negative effects on the teaching-learning process. Objective: to evaluate the quality of the ordinary examination of the Cell Tissues and Integumentary System subject through the level of difficulty and the power of the instrument discrimination. Methods: observational, descriptive cross-sectional study in the field of evaluation. The universe was made up of 369 exams that correspond to the total number of students who took part. The study variables were procedure and techniques, frequency of errors, index of difficulty and power of discrimination. For statistical processing, the calculation of indices and percentages was performed. Results: the exam consisted of seven questions, essay-type predominated (57.14%) and within these short-answer questions with a total of three that represents 75%. Question one had the highest number of correct answers while question four had the least number of correct answers. Of the questions, five (71.42%) were highly easy, two (28.57%) moderately easy, one (14.28%) medium difficulty. The exam was rated as highly easy with an index of 0.88. 85.71% of the questions presented an excellent discrimination as well as the exam in general with an index of 0.57. Conclusions: the exam showed an adequate quality based on the coherence that existed between the questions, the level of difficulty and the power of discrimination.